Gaps, challenges and opportunities towards achieving the 95-95-95 targets in Cameroon: A systematic review and meta-analysis protocol. - Ezechiel Ngoufack Jagni Semengue; Alex Durand N K A; Pamela Patricia Tueguem; Christelle Aude Ka'e; Evariste Molimbou; Lum Yah Forgwei; Naomi-Karell Etame; Aurelie Minelle Kengni Ngueko; Désiré Takou; Aristide Stephane Abah Abah; Alice Ketchadji; Pamen Bouba; et al. (PLoS ONE)
Background Given HIV elimination by 2030, the World Health Organization and the United Nations' Programme on HIV/AIDS (UNAIDS) have set three programmatic goals that all countries should have achieved before 2025; 95% of people living with HIV should know their status (target-1); 95% of people who know their status should be linked to treatment (target-2); and 95% of people on treatment should achieve viral load suppression (i.e. VL<1000 copies/ml; target-3). Despite considerable global progress over the past decade, many low-middle-income countries are still below the expected targets. This review protocol aims to provide a standardized document for in-depth analysis of the strengths, weaknesses, opportunities and threats (SWOT) towards achieving these programmatic targets in Cameroon. Methods This systematic review will include randomized and non-randomized trials, cohorts, case-controls, cross-sectional studies, case reports and governmental notices addressing the achievements, the gaps, the challenges and the opportunities towards the 95-95-95 targets in Cameroon. The search will consider studies from 2017 to 2024, retrieved from PubMed/MEDLINE, Cochrane Central Register of Controlled Trials, Google Scholar, online African journals, and Cumulative Index to Nursing and Allied Health Literature. We will include studies reporting HIV diagnosis, HIV link to treatment or HIV viral suppression in Cameroon. Results will be stratified according to time, age-group (adults' vs adolescents/children) and geographic locations. Primary outcomes will be "estimates on 95-95-95 programmatic goals at the national level". Secondary outcomes will consist of the SWOT analysis towards achieving these programmatic targets. A random-effects model will be used to calculate pooled prevalence if data permits. Conclusions This systematic review and meta-analysis protocol will guide global estimation on the achievement of the 95-95-95 targets as well as the stakes and challenges within the Cameroonian setting. Final evidence from the systematic review will allow identification of the gaps and measures to be taken to fasten our move towards the 95-95-95 in Cameroon by 2025. Systematic review registration Systematic review registration: CRD42024502755.